2023
DOI: 10.1212/wnl.0000000000201465
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Multiple Sclerosis From AQP4-Neuromyelitis Optica Spectrum Disorder and MOG-Antibody Disease With Imaging

Abstract: Background and objectives:Relapsing remitting multiple sclerosis (RRMS), aquaporin4 antibody-positive neuromyelitis optica spectrum disorder (AQP4-NMOSD) and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) may have overlapping clinical features. There is an unmet need for imaging markers that differentiate between them when serologic testing is unavailable or ambiguous. We assessed whether imaging characteristics typical of MS discriminate RRMS from AQP4-NMOSD and MOGAD, alone and in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 51 publications
2
54
0
Order By: Relevance
“…disease phenotypes at onset were optic neuritis and/or transverse myelitis for the majority of patients. 20 . Imaging characteristics are age-dependent in MOGAD, with the highest frequency of brain involvement in children, ranging from poorly demarcated and widespread lesions in the childhood to small nonspecific cerebral lesions in older children and adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…disease phenotypes at onset were optic neuritis and/or transverse myelitis for the majority of patients. 20 . Imaging characteristics are age-dependent in MOGAD, with the highest frequency of brain involvement in children, ranging from poorly demarcated and widespread lesions in the childhood to small nonspecific cerebral lesions in older children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only few and relatively small studies have assessed MOGAD patients in the non-acute phases. 16,[18][19][20] Against this background, we carried out a study aiming at identifying key features able to distinguish non-acute adult MOGAD from AQP4-NMOSD and RRMS. Our ultimate goal was to provide advice on how to identify MOGAD patients in clinical practice, by suggesting sequential tests and supporting features beyond or in addition to serological testing.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…When Select6* and Select3* algorithms were used, they were not superior to the cutoff calculated when all lesions were considered. 3 In conclusion, CVS remains mainly a research biomarker, which is both personnel and time-intensive and requires optimal pulse sequences that are not widely available on clinical scanners. 6 Given that the 2017 McDonald criteria can accurately diagnose paediatric MS (with the inclusion of intrathecal oligoclonal bands and serum myelin oligodendrocyte glycoprotein, MOG, antibody testing), we would suggest that CVS is used as an additive metric for selected cases, in whom the diagnosis may be challenging, for MS confirmation, rather than part of recommended imaging protocols.…”
mentioning
confidence: 99%
“… 2 A recent two-centre prospective study of 91 adult patients with acquired demyelinating disorders demonstrated that CVS was one of the most accurate measures differentiating MS from seropositive neuromyelitis optica spectrum disorder (AQP4 + NMOSD) (84% vs 33%, accuracy/specificity/sensitivity: 91/88/93%, p < 0.001). 3 To date, few studies have looked at the diagnostic accuracy of CVS in paediatric-onset MS.…”
mentioning
confidence: 99%
See 1 more Smart Citation